Induction and rooting of Cordia alliodora (Ruiz Et Pavon) Oken - Carranza Patiño, Mercedes Susana (2016)
Cordia alliodora (laurel) wood attractive appearance, its physical and mechanical characteristics, its abundant natural regeneration, as well as the contribution to carbon sequestration and soil protection, have made it an ideal species for reforestation. However, there is insufficient good quality planting material to meet these needs and to respond to the average annual demand. Hence, vegetative propagation has become an essential tool in breeding and it is being widely used for the conservation of genotypes in clonal banks. To this end, a methodology for laurel tree epicormic shoot induction and rooting, using plant growth regulators was established. Cytokinin concentrations used for induction of shoots from adult trees were 0, 3000, 6000, 9000 mg L-1 of BAP alone and combined with 1000, 2000, 3000 mg L-1 of IAA a Complete Randomized Design (DCA) with seven treatments and three repetitions, considering each tree as a repetition, was applied. The concentrations of auxin for rooting of shoots were 0, 1000, and 1500 mg kg-1 of NAA and IBA. A factorial arrangement DCA 3 x 3 (NAA x hormone IBA) with five repetitions and five units per repetition was used. After 105 days, the induction of epicormic shoots and epicormic buds response was evaluated 2.67 buds   16.42 cm long with 6000 mg kg-1 of BAP + 2000 mg kg-1 of IAA were obtained. At 45 days rooting percentage was 54%, the number of roots was 1.78, 2.49 length 2.59 and force with 1500 mg kg-1 of NAA + 1500 mg kg-1 of IBA. This research demonstrated that using cytokinins and auxins is effective in laurel epicormic shoots induction and rooting.